Odpowiedzialność społeczna jako źródło przewagi konkurencyjnej - Paliwoda-Matiolańska, Adriana (Social Responsibility as a Source of Competitive Advantage, 2009)
Nowadays technological and economic development has increased an importance of giving social legitimacy to business activity. It changes a status and role of a corporation in modern society. Stakeholders theory is a new, dynamic approach to current management dilemmas. The paper presents a thesis that a corporation is able to achieve persistent competitive advantage on the strength of stakeholders management and sustainable development. Stakeholder management and sustainable development as a part of strategic management create innovation, social capital, entrepreneur spirit and environment, reputation of company that leads to the creation of financial and social value.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 168-183